Augmented Reality Assisted Mathematics Learning Media in The Covid-19 Pandemic - Sumliyah Liyah; Titi Rohaeti; Fatikasari (Ilmu Inovasi Nusantara, 2021)
Utilization of cultural literacy is still low in the school environment. However, learning at Veterans Vocational High School is done online due to the Covid-19 pandemic which requires students to study at their respective homes. Augmented Reality as an alternative media for learning mathematics. The purpose of this study was to determine the use of cultural literacy as a medium for learning mathematics assisted by augmented reality in Veterans Vocational School. The design of this research is qualitative research. In this study, researchers tried to describe, identify, and classify the use of mathematics learning media in Veterans Vocational School. By taking a sample of 1 mathematics teacher and 9 students of class XI AKL. The researcher used the instrument in this study was a non-test instrument. The application of augmented reality learning media is only at the learning theory stage in the stimulus stage where mathematics learning material geometric transformation can be done by applying learning media using Cultural Literacy, namely